PENGARUHlCURRENTlRATIO, NETtPROFITtMARGIN, RETURN ON ASSET, TOTAL ASET TURNOVERr DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (Studieempirisspada.Perusahaan LQ 45 yang.Terdaftar.di.Bursa,Efek Indonesia Periode 2017-2021) - Astrid Dita Merinia Hakim; Reni Santoso (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Capital.structure.is.a.comparisonl or consideration betweenn owned capital.and foreign capitall. Capital structure issoneeof the financial decisions faceddbyyfinancial managers related to theecomponents of money, preferreddshares and.ordinary shares used by the company. The purpose of this study is to determine the effect of current ratio, net profit margin, retrun on assets, total asset turnover and company size on capital structure. This research was conducted on LQ 45 companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The number of samples used in this study was as many as 13 companies from a population of 45 companies, through the purposive sampling method. The collection of research data was carried out using the nonparticipation observation method through the company's financial statements. The analysis technique applied is the panel data regression technique. The results of this study suggest that the current ratio, net profit margin, total asset turnover affect the capital structure. Meanwhile, retrun on assets and company size does not affect the capital structure.